(untitled) (Research, Society and Development, 2020)
The State of Rio de Janeiro has the highest proportion of municipalities with the worst vulnerability indexes to Covid-19 (VIC) in the south and southeast regions. Objective: to describe the patterns of occurrence of the COVID-19 pandemic in the 18 municipalities in the Metropolitan Region of Rio do Janeiro, considering the vulnerability to the virus. Results: The graphs show a tendency for the epidemic to stabilize, with the exception of São Gonçalo, which has an increasing trend and Itaguaí, a decreasing one. There was a moderate, positive and significant association between the vulnerability indicators suggesting that the highest incidences occurred in less vulnerable municipalities, in municipalities with a lower proportion of black and brown population and with a higher number of primary care units (UBS)/ inhabitant. Conclusion: COVID-19 has spread unevenly. Less vulnerable municipalities had more cases and only one municipality in the region tended to reduce cases. The importance of disseminating information about the functioning of the UBS and the care and monitoring policies for symptomatic patients, in addition to testing the contacts, became clear to allow an adequate monitoring of the patterns of spread of the disease in order to contribute to the orientation of control activities directed at the coping with the epidemic.